Development of sustainable 3R-based construction waste management framework for Penang - Ng, Lee Shan (2021)
Weak implementation of construction waste reduction among contractors will lead to unsustainable construction waste management. Consequences include increase in the construction waste in landfills which is critical especially on islands where land is very limited for solid waste disposal activities. This study has 4 objectives: (1) to identify current 3R practices among contractors in Penang in managing construction waste; (2) to determine constraints of 3R implementation; (3) to identify elements of 3R best practices; and (4) to develop a framework for best practice among contractors in reducing construction wastes through 3R. Semi-structure interviews were carried out with experts from Penang Local Authority, CIDB Penang and Headquarters, National Solid Waste Management Department, and Headquarters of SWCorp. A total of 143 valid response questionnaires were collected from construction contractors of grade G7, G6 and G5 in Penang. These 143 responses are equivalent to 65% response rate. Survey showed that only 39.8% construction contractors have been practicing 3R in managing their waste where concurrent with expert interviewed. 3R practice is not mandatory in construction waste management in Penang. According to respondents, constraints to 3R implementation in managing construction waste are time and cost; contractors’ attitude and low participation; lack of awareness and knowledge; lack of enforcement and supporting regulation; lack of coordination; and lack of space. However, respondent contractors and experts interviewed have different views in the constraint of lack of space. The majority of respondents agreed that elements of best practice in 3R include law and regulation; scheme and incentive; participation and practice of contractors; awareness and knowledge; and current technology adoption where the mean score ≥ 3.75. Law and regulation are the most important element which have reliable relationship with other elements. A framework of best practice has been developed for construction waste reduction through 3R in order to improve the implementation of 3R among construction contractor in Penang